2015
DOI: 10.1108/ijshe-06-2013-0071
|View full text |Cite
|
Sign up to set email alerts
|

Food-related environmental beliefs and behaviours among university undergraduates

Abstract: Purpose -The purpose of this paper was to document the food-related environmental beliefs and behaviours of undergraduate university students. More specifically, this research was focussed on determining if environmental sustainability is a consideration in students' food choices, identifying the specific choices and behaviours adopted to reduce their food-related environmental footprint, and documenting the role of gender and pro-environmental values in these food-related environmental beliefs and behaviours.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 54 publications
4
50
0
2
Order By: Relevance
“…In a systematic review of consumer perceptions of sustainable protein consumption, Hartmann and Siegrist [37] found that it is common for consumers to underestimate the ecological impact of meat consumption. This has been observed in many different studies [33,[38][39][40] and may imply a lack of knowledge about the environmental impact of meat consumption. Alternatively, this could reflect that consumers are generally unwilling to reduce their meat consumption [40] and are subsequently motivated to minimise their perceptions of the negative consequences of their choices [41].…”
Section: Motivations and Constraintsmentioning
confidence: 98%
“…In a systematic review of consumer perceptions of sustainable protein consumption, Hartmann and Siegrist [37] found that it is common for consumers to underestimate the ecological impact of meat consumption. This has been observed in many different studies [33,[38][39][40] and may imply a lack of knowledge about the environmental impact of meat consumption. Alternatively, this could reflect that consumers are generally unwilling to reduce their meat consumption [40] and are subsequently motivated to minimise their perceptions of the negative consequences of their choices [41].…”
Section: Motivations and Constraintsmentioning
confidence: 98%
“…For example, there is some evidence that repositioning meat options to appear after rather than before vegetarian options on menus or in buffets to make these items more prominent may increase the number of people selecting meat-free meals, but more research is needed (88). Decreasing portion size of meat products in a restaurant has been shown to decrease meat consumption with no detrimental impact on customers' perception of their restaurant experience, perhaps because the meat is a small part of the overall event (89).…”
Section: Changing Dietsmentioning
confidence: 99%
“…Many higher education institutions have implemented sustainability initiatives in recent years (Campbell-Arvai, 2015;Levy and Marans, 2012). Other institutions have faced roadblocks in incorporating sustainability but have an interest in making progress in this area (Larrán et al, 2015;Lidgren et al, 2006;Schmitt-Figueiró and Raufflet, 2015).…”
Section: Introductionmentioning
confidence: 99%